Synthesis, and antimicrobial evaluation of new pyridine imidazo [2,1b]-1,3,4-thiadiazole derivatives - Varun Bhardwaj; Malleshappa N. Noolvi; Sunny Jalhan; Harun M. Patel (Journal of Saudi Chemical Society)
With the aim of producing new biologically active compounds, a series of New Pyridine Imidazo [2,1b]-1,3,4-thiadiazole derivatives 4(a–k) were synthesized. All the compounds were characterized via IR, 1H-NMR and Mass spectral studies. The antimicrobial activity of newly synthesized compounds against various bacteria; Bacillus pumillus, Staphylococcus aureus, Vibrio cholera, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, and fungi; Candida albicans were evaluated. Among the compounds tested, 4(a), 4(b), 4(f), 4(h) and 4(k) exhibited good antimicrobial activity while others responded moderately with reference to standard drugs ampicillin and amphotericin B.